A note on the nomenclature of Justicia micrantha Wall. ex C.B. Clarke (Acanthaceae) and its lectotypification - Soumya, Puliyakode; Sunojkumar, Purayidathkandy (Phytotaxa, 2020)
Rostellaria crinita Nees (1832: 101) was described with referencing to Wallich’s designation “Justicia micrantha” Wall. (1830: 2449), which is a nomen nudum without diagnosis or description. As the name Rostellaria Nees (1832: 100) was pre-occupied for a different genus, Nees (1847) transferred all species under Rostellaria Nees to Rostellularia Reichb. (1837: 190). But, Clarke (1885) in Hooker’s Flora of British India reused Wallich’s name for the same species, Justicia micrantha Wall. ex C.B. Clarke (1885: 536). Under Art. 6.11 of ICN (Turland et al. 2018), this name is a replacement name for Rostellaria crinita because of existence of the name Justicia crinita Thunberg (1794: 338). While revising the genus Justicia for the Flora of Hassan District, Ramamoorthy (1976) considered Justicia micrantha Wall. ex C.B. Clarke to be the later homonym of Justicia micrantha Pohl ex Nees (1847: 408) and hence he proposed a new name, Justicia neesii Ramamoorthy (1976: 551). As part of the ongoing systematic studies on the genus Justicia in Peninsular India, we found that the name Justicia micrantha Pohl ex Nees was not validly published because it was cited in the synonymy when published according to Art. 36.1(b). Therefore, the name Justicia neesii is an illegitimate superfluous name according to Art. 52.1, 52.2 of ICN (Turland et al. 2018).